Searching for biomarkers in the progression from polycystic ovary syndrome to endometrial carcinoma - Zhenzhen Lu; Ying Gao (Clinical and Experimental Obstetrics & Gynecology)
Background: Polycystic ovary syndrome is a female reproductive system disease closely related to endocrine and highly correlated with the development of endometrial carcinoma in women, it is important to identify the key genes involved in the development of polycystic ovary syndrome. Methods: To identify the hub genes, microarray datasets GSE48301, GSE115810 and GSE3013 were downloaded from Gene Expression Omnibus database. We performed in-depth cross-tabulation bioinformatic analysis to identify differentially expressed genes (DEGs) among four types of endometrial cells in GSE48301 and two endometrial carcinoma datasets GSE115810 and GSE3013, followed by gene ontology, KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment, protein-protein interaction network analysis. Results: Thirteen seed DEGs and 4 significantly expressed DEGs were identified, and potential drugs and mRNAs were found. Conclusion: EDNRA, FBN1, PMP22, SPARC and IGF-1 may be potential and their miRNAs, especially hsa-miR-29a-3p and hsa-miR-29b-3p may be potential biomarkers in the progression from PCOS to endometrial carcinoma.